THE EFFORTS TO IMPROVE EMPLOYEE PERFORMANCE THROUGH EMPLOYEE ENGAGEMENT AND ORGANIZATIONAL COMMITMENT OF CV. NIPSON PAINT SURABAYA PRODUCTION DEPARTMENT - Yusieni .; Joseph L. Eko Nugroho (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2017)
This study aims to examine the effect of employee engagement and organizational commitment to improving employee performance. The statistical analysis used in this study was SEM (Structural Equation Modeling) by collecting data through questionnaires to 167 CV. Nipson Paint production department employees as respondents. The results of the analysis proved that employee engagement had a significant positive effect on organizational commitment and employee performance, besides that there was a significant positive effect between employee engagement and organizational commitment.